The Effect of Grafting Watermelon onto Some Cucurbit Rootstocks on Vegetative growth Traits Using Zeolite under Water Stress Conditions: Pengaruh Pencangkokan Semangka pada Beberapa Batang Bawah Mentimun terhadap Sifat Pertumbuhan Vegetatif Menggunakan Zeolit pada Kondisi Cekaman Air - Al-Baghdadi, Nashwan Abdul-Hameed Abbas; Al-Obaidi , Hameed Saleh Hammad; Abood, Mohammed Ali (Procedia of Engineering and Life Science, 2024)
General Background: Watermelon production in arid regions faces challenges due to water scarcity and soil fertility issues, prompting the need for agronomic strategies that improve resilience and productivity. Specific Background: Techniques like grafting watermelon onto cucurbit rootstocks and applying zeolite as a soil amendment have shown potential in mitigating water stress and enhancing growth. However, comprehensive studies on the combined effects of these practices under varying water regimes remain limited. Knowledge Gap: The interplay between grafting types, zeolite concentrations, and irrigation levels on watermelon vegetative growth and yield characteristics under water stress has yet to be fully explored. Aims: This study aimed to evaluate the effects of grafting watermelon onto three cucurbit rootstocks (Cucurbita pepo, pumpkin, and pumpkin seed) and applying zeolite at three concentrations (0, 20, and 40 g per plant) under two irrigation levels (full and half) to identify optimal growth conditions. Results: The experiment, arranged in a factorial RCBD, revealed that grafting and zeolite addition significantly improved vegetative traits like leaf number, branch length, and branch count, especially under water stress. The best performance was observed with pumpkin grafting and 40 g of zeolite under reduced irrigation, achieving significant increases in leaf length, width, and branch numbers. Novelty: This study uniquely combines grafting with zeolite application under water stress conditions, demonstrating that watermelon grafted onto specific rootstocks, when supplemented with zeolite, can sustain growth and yield despite reduced irrigation. Implications: The findings suggest that using zeolite and grafting on stress-tolerant rootstocks could enable more efficient water use in watermelon cultivation, promoting sustainable agricultural practices in water-limited regions. Highlights: <div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="0febd948-1dd2-48d3-a3f7-e51f8678efa0" data-message-model-slug="gpt-4o"> Grafting with zeolite boosts watermelon growth under water stress. Best results: 40 g zeolite, half irrigation, enhanced water efficiency. Strategy aids sustainable watermelon farming in arid regions. Keyword: Watermelon grafting, Cucurbit rootstocks, Zeolite application, Water stress, Yield improvement